2009
DOI: 10.1103/physrevlett.102.137401
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Determination of the Polaron-Induced Optical Absorption of Organic Charge-Transport Materials

Abstract: We examine polaron-induced absorption in organic transport materials using a highly sensitive measurement technique. A hole only device is embedded into a low-loss TE2 waveguide structure, and the current induced change of the waveguide absorption is measured. The exemplary study of 2,2('),7,7(')-tetrakis(N,N-diphenylamine)-9,9(')-spiro-bifluorene (S-TAD) reveals a very low polaron absorption cross section of sigma(p) < or = 2.6 x 10(-18) cm(2) for 560 nm < or = lambda < or = 660 nm. The accuracy of this data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Indeed, the optical time decay is related to the onset of the polaronic absorption that reduces the singlet population and hence reduces the EL [11,16].…”
Section: Optical Responsementioning
confidence: 99%
“…Indeed, the optical time decay is related to the onset of the polaronic absorption that reduces the singlet population and hence reduces the EL [11,16].…”
Section: Optical Responsementioning
confidence: 99%
“…9 Thus, Joule heating is suppressed in devices with a small active area, as we confirmed previously. [9][10][11][12][13]25 Furthermore, under pulse operation with a pulse width of 5 ls, a very high J max of 2.8 kA cm À2 was achieved in the linear device with X ¼ 50 nm because of further suppression of device heating. Figure 4(b) depicts external EL quantum efficiency (g ext ) À J characteristics of the devices with X ¼ 50 nm, 100 nm, 200 nm, 500 nm, and 1 lm.…”
mentioning
confidence: 99%
“…Exciton-polaron annihilation is the most critical issue to overcome because all polarons have a broad absorption spectrum. [8][9][10][11] In our previous study, we demonstrated high current injection of over 1000 A cm À2 without device breakdown into OLEDs with an unusual device configuration of a small active area (200 Â 200 nm) on a high thermally conductive substrate by application of a short pulse voltage of less than 1 ls. 12,13 However, very serious efficiency roll-off was observed at such high current density.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They may find applications in the fields of, e.g., polymer optical fiber telecommunications [2], bio/chemo-sensing [3] or spectroscopy [4]. In the perspective of achieving direct [5] or indirect [6] electrical pumping of organic semiconductors, most of recent studies have been dealing with low-loss resonator structures such as distributed feedback resonators [7,8] or microcavities [9,10]. In the meantime, less attention has been paid to the question of optimizing conversion efficiency, beam quality and power scaling capability.…”
mentioning
confidence: 99%